2022
DOI: 10.1093/jxb/erac117
|View full text |Cite
|
Sign up to set email alerts
|

Combining analyses of metabolite profiles and phosphorus fractions to explore high phosphorus utilization efficiency in maize

Abstract: Phosphorus (P) limitation is a significant factor restricting crop production in agricultural systems, and enhancing the internal P-utilization efficiency (PUE) of crops plays an important role in ensuring sustainable P use in agriculture. To better understand how P is remobilized to affect crop growth, we first screened P-efficient (B73 and GEMS50) and P-inefficient (Liao5114) maize genotypes at the same shoot P content, and then analyzed P pools and performed non-targeted metabonomic analyses to explore chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…In fact, so far, there have only been reported metabolomics and/or transcriptomic and ionomic studies focused on selected subsets of accessions/cultivars displaying high or low tolerance to limiting Pi growth conditions. In general, these studies identified some significant correlations between gene co-expression modules, metabolites, and/or elements with plant performance traits under low Pi growth conditions, which inform on metabolic pathways and transcriptional programs and potential TF regulators underlying low Pi tolerance, functional validation is still missing for most candidates (Hajheidari et al 2022;Han et al 2022;He et al 2022;Luo et al 2019). Only in one GWAS study in maize, the information on Pi starvation-responsive metabolites and the significant correlation between specific metabolites and plant performance traits has been used to identify potential candidate causal genes underlying QTLs for these traits.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, so far, there have only been reported metabolomics and/or transcriptomic and ionomic studies focused on selected subsets of accessions/cultivars displaying high or low tolerance to limiting Pi growth conditions. In general, these studies identified some significant correlations between gene co-expression modules, metabolites, and/or elements with plant performance traits under low Pi growth conditions, which inform on metabolic pathways and transcriptional programs and potential TF regulators underlying low Pi tolerance, functional validation is still missing for most candidates (Hajheidari et al 2022;Han et al 2022;He et al 2022;Luo et al 2019). Only in one GWAS study in maize, the information on Pi starvation-responsive metabolites and the significant correlation between specific metabolites and plant performance traits has been used to identify potential candidate causal genes underlying QTLs for these traits.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, increased P allocation to nucleic acids (rRNA) in chickpea leaves may be associated with fast protein synthesis and turnover, e.g., the production of ribulose-1,5bisphosphate carboxylase oxygenase (Rubisco) and various Calvin-Benson cycle enzymes, A c c e p t e d M a n u s c r i p t and the replacement of damaged photosystem proteins (Nelson & Millar, 2015;Lambers, 2022), to sustain a rapid photosynthetic rate under low P conditions. Reduced P investment in the lipid P fraction through lipid remodeling and/or replacement by lipids that do not contain P, had been demonstrated as an important adaptation mechanism for plants to decrease overall foliar P demand, without compromising a relatively rapid photosynthetic rate at the species level (Lambers et al, 2012;Hidaka & Kitayama, 2013) and genotype level (Jeong et al, 2017;Han et al, 2022;Hayes et al, 2022). Inconsistent with this pattern, we found little difference in the concentration and percentage of lipid P among chickpea genotypes with contrasting PPUE, suggesting intraspecific variation in lipid P investment may not play a key role in determining PPUE among chickpea genotypes.…”
Section: Does the Allocation Of Foliar P Fractions Explain Contrastin...mentioning
confidence: 99%
“…Increasing evidence shows that to achieve relatively fast rates of photosynthesis with high PPUE requires a delicate balance in investment among foliar P fractions (Stitt et al, 2010;Hidaka & Kitayama, 2013;Zhang et al, 2021;Hayes et al, 2022). For instance, some plants suffering from P deficiency can decrease their overall requirement for foliar P by reducing investment in non-metabolite P fractions (e.g., nucleic acid P and lipid P) to different degrees and thus buffering the direct P-restriction of photosynthesis (Warren, 2011;Hidaka & Kitayama, 2013;Mo et al, 2019;Zhang et al, 2021;Han et al, 2022). Lipid remodeling is an essential adaptation mechanism to cope with P starvation in many species (Tjellström et al, 2008;Nakamura et al, 2009;Jeong et al, 2017;Tawaraya et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate fertilizer use can exert negative pressure on crop production [19], and low fertilization efficiency is a problem in tropical regions [20]. Efficient and effective nutrient management lies at the core of best agricultural practices and facilitates sustainable intensification [21], [22]. Comprehensive maize cultivation technologies can help enhance maize production [23], and to address the challenges, controlledrelease fertilizers or slow-release fertilizers have been developed [24].…”
Section: Introductionmentioning
confidence: 99%